Analisis Kebijakan Program Pendidikan Agama Islam Untuk Meningkatkan Partisipasi Orang Tua dan Masyarakat - Risa Arisanti; Sofyan Sauri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Education is a shared responsibility between schools, families, communities and governments. Facing challenges in the world of education in the future, it takes the support of parents and the community in achieving educational goals. This study analyzes Education policies to increase parental and community participation, using qualitative methods with library research. The results of the study indicate that currently the participation of the community in education has been stated in various government policies, but in its implementation the participation of parents and the community is still not optimal. So that in its implementation, further policy efforts are needed from the school to increase the role of parents and the community. Efforts to increase the role of parents and the community through school committees need to be realized in School-Based Management: (1) building school ownership attitudes, (2) formulating school policies, (3) building quality awareness, (4) attention to academic life, and (5) build school institutional work arrangements. Related to the purpose of education to form the character of students who have noble character, it is necessary to have good cooperation and coordination between the school, parents and the community in the success of value-based education. The school must integrate the content of the value curriculum in each lesson. There is good cooperation with parents in education that is in line in the family. Value education in society provides children with an understanding of the implementation of value education in society. Keywords: Policy, Participation, Parent, Education